Theology of Pluralism in Indonesia: Inclusive and Exclusive Islam in Dialogue - Ardiansyah Ardiansyah; Viki Bayu Mahendra (Sinergi International Journal of Islamic Studies, 2026)
Indonesia’s religious plurality makes the relationship between Islamic theology and public coexistence a significant scholarly and civic concern. This article addresses a gap in Indonesian pluralism scholarship by comparatively examining how inclusive and exclusive Islamic theological orientations are configured, mediated, and linked to public coexistence within one analytical framework. Using a structured qualitative review of a final corpus of 31 scholarly and policy-relevant sources, published mainly between 2016 and 2025 and supplemented by foundational theoretical texts, the study analyzes recurring differences in truth claims, scriptural reasoning, attitudes toward local culture, and public ethics. The reviewed literature suggests that inclusive orientations are more frequently associated with contextual interpretation, dialogical engagement, and civic accommodation, whereas exclusive orientations are more often linked to literalist reasoning, sharper symbolic boundary-making, and greater discomfort with religious difference. Rather than proposing a universal model, the article offers a bounded contextual theology of pluralism for Indonesia by selectively relating Hick’s pluralist insight to Islam Wasathiyah, Islam Nusantara, and inclusive citizenship. Because the study is interpretive and literature-based, its conclusions are presented as analytical tendencies and policy-relevant possibilities rather than as direct empirical measurement of Indonesian Muslim attitudes or outcomes.